Aggregation-Induced Emission of Au/Ag Alloy Nanoclusters for Fluorescence Detection of Inorganic Pyrophosphate and Pyrophosphatase Activity - Lei, Zhongli; Zhou, Jie; Liang, Miao; Xiao, Yan; Liu, Zhihong (Frontiers in Bioengineering and Biotechnology, 2021)
The development of sensitive and accurate detection of inorganic pyrophosphate (PPi) and pyrophosphatase activity (PPase) is important as they play vital roles in biological systems. However, it is still not satisfactory for most of the analytical methods for PPi and PPase because of their Cu2+-dependence and poor accuracy. Although the metal ion triggered aggregation-induced emission (AIE) of metal nanoclusters (NCs) offers a new approach to design a Cu2+-free strategy for the accurate determination of PPi and PPase recently, current methods are all focused on utilizing pure metal NCs. Alloy NCs incorporating the advantages of diverse metal usually can achieve improved behaviors in the application, such as enhanced sensitivity and stability. In this work, glutathione stabilized alloy Au/Ag NCs were synthesized via a simple method and used for the fluorescence detection of PPi and PPase based on a Zn2+-regulated AIE strategy. The controlled release of Zn2+ by PPi and PPase could regulate the AIE of Au/Ag NCs and be employed to response PPi concentration and PPase activity. This method processes simple procedure, high sensitivity and stability, and low toxicity. In addition, we also studied the AIE behaviors of this Au/Ag NCs and offer some fundamental understanding of the AIE properties of water-soluble alloy NCs. This study not only provides a straightforward and new approach for PPi and PPase determination but a basis for further study on the AIE properties of alloy NCs and their application.